An open-label, randomized, post-authorization study of mirabegron in Chinese participants with overactive bladder - Zhipeng Zhang; Deyi Luo; Zhong Chen; Peng Zhang; Ganping Zhong; Keji Xie; Zhuoqun Xu; Xudong Li; Jianye Wang; Yingfan Yang; Farid Abdul Hadi; Arianne Schild (Asian Journal of Urology)
Objective: To assess efficacy and safety of mirabegron 25 mg/day and 50 mg/day for overactive bladder in Chinese participants. Methods: Participants of ≥18 years with overactive bladder symptoms lasting for ≥12 weeks, a mean of ≥8 micturitions per 24 h, and a mean of at least one episode of Grade 3 or 4 urgency or urge incontinence per 24 h based on the Patient Perception of Intensity of Urgency Scale over a 3-day micturition diary period were randomized 2:1 to open-label treatment with oral mirabegron 50 mg or 25 mg once daily for 12 weeks (15 sites in China, January 2021–March 2022). A dose escalation from 25 mg/day to 50 mg/day was permitted at weeks 4 and 8 according to the investigators' discretion. The primary efficacy endpoint was the change from baseline to Week 12 in the mean number of micturitions per 24 h in those randomized to mirabegron 50 mg/day. Secondary efficacy endpoints were the change in mean number of micturitions at weeks 4 and 8 in the mirabegron 50 mg/day group and weeks 4, 8, and 12 in the mirabegron 25 mg/day group, change from baseline to weeks 4, 8, and 12 in Grade 3 or 4 urgency episodes on the Patient Perception of Intensity of Urgency Scale, episodes of daytime incontinence, nighttime incontinence, and urgency incontinence, and Overactive Bladder Symptom Score for mirabegron 50 mg/day and 25 mg/day groups. Results: Statistically significant reduction (p<0.001) from baseline to Week 12 was observed in mean micturitions per 24 h for participants randomized to mirabegron 50 mg/day: mean±standard error: 11.71±0.43 at baseline, 7.80±0.24 at Week 12; adjusted mean change: −3.73 (95% confidence interval −4.30 to −3.16). Both doses showed statistically significant improvement in secondary efficacy endpoints at weeks 4, 8, and 12 versus baseline. Safety was consistent with mirabegron's known safety profile. Conclusion: The results support a mirabegron dosage of 50 mg/day for the treatment of OAB in China.